Navigating 'ethics in practice': An ethnographic case study with young women living with HIV in Zambia. Issue 12 (2nd December 2019) - Mackworth-Young, Constance R.S.; Schneiders, Mira L.; Wringe, Alison; Simwinga, Musonda; Bond, Virginia
ABSTRACT: While 'procedural ethics' provides essential frameworks for governing global health research, reflecting on 'ethics in practice' offers important insights into addressing ethically important moments that arise in everyday research. Particularly for ethnographic research, renowned for it's fluid and spontaneous nature, engaging with 'ethics in practice' has the potential to enhance research practice within global health. We provide a case study for such reflexivity, exploring 'ethics in practice' of ethnographic research with middle-income young women living with HIV in Lusaka, Zambia. We explore the ethical issues arising from the layered interaction of the population (young women), the disease under investigation (HIV), the method of study (ethnographic), and the setting (Zambia, a lower middle income country). We describe how we navigated five key practical ethical tensions that arose, namely the psycho-emotional benefits of the research, the negotiated researcher-participant relationship, protecting participants' HIV status, confidentiality and data ownership, and researcher obligations after the end of the research. We exemplify reflexive engagement with 'ethics in practice' and suggest that engaging with ethics in this way can make important contributions towards developing more adequate ethical guidelines and research practice in global public health.